Selection of greenhouse hybrids of melon in the Republic of Uzbekistan - Liang Ekaterina; Ganiev Farkhod; Abilova Marjan; Kim Dima (BIO Web of Conferences)
To date, not a single local variety of melon for protected ground has been zoned in our republic. In this regard, we conducted research to create hybrids of melon for protected ground. Several promising melon lines were selected from foreign and local selection (open ground). Subsequently, hybrid combinations were created. In the hybrid nursery, several promising local hybrids of melon were studied in comparison with the Kichkintoy standard. In 2022, the first variety of melon for protected ground was created for the first time, which was transferred to the State Agency for Variety Testing under the name Zarkhal. At present, we have created several hybrid combinations of greenhouse melons F1 Zarhal×L-22-17, F1 Zarhal×L-22-20, F1 L-160×L-179, F1 L-161×L-179, which are distinguished not only by the yield of 8–10 kg/m2, but also by high taste qualities with an average weight of 0.8–1.5 kilograms, resistance to diseases (powdery mildew, fusarium wilt) - the tasting score of which was 4.8–5.0 points.